Sosialisasi Penyuluhan Pemasaran Digital Melalui Kuliah Kerja Nyata Tematik Pada Desa Pemulutan Ulu Kecamatan Pemulutan Kabupaten Ogan Ilir - Zaini, Kurniawan; Agustina, Merry; Sahfitri, Vivi; Purwaningtias, Fitri; Nopasari, Widia; Lestari, Regina; Ruspiana, Mellia (Jurnal Nasional Pengabdian Masyarakat, 2024)
One of the Three Pillars of Bina Darma University is community service through Thematic Community Service Programs (KKNT). KKNT aims to help students gain knowledge, skills, and social awareness through new learning experiences. The community expects the presence of students to enhance motivation and innovation in the development field. Students, as active communication bridges, play a crucial role in developing and applying technology and science. The university, as an agent of change, supports this role. KKNT must be implemented using four principles: feasible, acceptable, sustainable, and participatory. The KKNT implementation process generally consists of three stages: evaluation, reporting, and follow-up. Two types of reports are prepared during the reporting stage: group reports by student groups and individual reports by each student. To conduct observations, question-and-answer methods, documentation, and direct field observations are used. Observations indicate that KKNT work programs include both physical and non-physical programs